Phyto-fabrication of copper oxide nanoparticles (NPs) utilizing the green approach exhibits antioxidant, antimicrobial, and antifungal activity in Diospyros kaki fruit - Iftikhar Hussain Shah; Irfan Ali Sabir; Muhammad Ashraf; Asad Rehman; Zishan Ahmad; Muhammad Azam; Ghulam Abbas Ashraf; Haroon ur Rasheed; Guohui Li; Jeridi Mouna; Mohammad Faizan; Muhammad Ahsan Altaf; et al. (Fruit Research)
Nanotechnology has emerged as a prominent field in recent times. The fabrication of biocompatible materials has taken on highlighted significance owing to their requisite application in diverse sectors including medicine, water treatment and purification, health, and other related fields. There has been a lot of research done recently on the green synthesis of various nanoparticles (NPs). Copper a high-performance metal used in agriculture to combat pathogenic attacks, has received less attention. The current work demonstrates the successful preparation of green synthesized copper oxide nanoparticles (CuO.NPs) from Mangifera indica (M. indica) leaf extract. The spectral and morphological characterization biosynthesized were observed using, FTIR, XRD, and TEM analysis. The FTIR analysis revealed the functional groups present in plant extracts. XRD was carried out to demonstrate the crystalline nature and size of nanoparticles using the Scherrer formula. UV was performed to observe the optical properties of NPs. Further, Transmission electron spectroscopy (TEM) was carried out to confirm the physical shape of CuO.NPs with 50 nm. The M. indica mediated NPs were evaluated against gram-negative and positive bacteria Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) at different concentrations. The in vivo fungicidal activity was performed against Rhizophus oryzae (R. oryzae) on Diospyros kaki (persimmon fruit). The detach fruit method was applied to evaluate the potential of NPs. Higher exposure of 100 µg·mL−1 CuO.NPs showed mycelia inhibition followed by 30, 60, and control treatments. Furthermore, Green CuO.NPs showed prominent antioxidant activities as compared to plant sources. The findings obtained suggest that the green-formulated CuO.NPs could be further investigated for the treatment of many phytopathogenic diseases.